HERMENEUTIKA HADIṠ DALAM PEMIKIRAN MUHAMMAD MUSTAFA AL ‘AZAMI - Zainal Abidin; Ahmad Majidun (Wahana Islamika: Jurnal Studi Keislaman, 2021)
The writing basically wants to prove that 'Aẓami issubstantially doing hermeneutic work. The hadīṡ 'Aẓamistudy method, both sanad and matan will be drawn in thediscussion of hadīṡ hermeneutics, in which case the authoruses three basic elements in hermeneutical discourse, namelythe author (narrator), the text (hadīṡ) and the reader ('Aẓami).The purpose of this writing is to find out how hadīṡhermeneutics in the Thoughts of Muh}ammad Mus}t}afa> Al'Aẓami. The writing method uses a literature review for'Aẓami's works, namely Studies on Early Hadīṡ Literature(Hadīṡ Nabawi and the History of Codification) and Studieson Methodology and hadīṡ Literature as primary sources. Inaddition to these primary sources, the author also usessecondary sources in the form of works related to writingproblems. The data analysis uses a technique in the form ofcontent analysis. The results of the analysis show that 'Aẓami,in her hermeneutical work, uses several methods, namely 1)Comparison between hadīṡ-hadīṡ of Various Translators'Disciples. 2) Comparison of Statements from Narrators Aftera Certain Period. 3) Comparison between Written Documentsand Conveyed from Memorize. 4) Comparison of Hadīṡ withQur'anic Verses and 5) Rational Approach in Criticism ofhadīṡ